Disappearing Bone Disease with Disappearing Spleen! - John, BM; Singh, Daljit (Journal of Nepal Paediatric Society, 2009)
A 6-year-old girl who reported for pain abdomen was incidentally detected to have multiple osteolytic lesions on X-ray. She was diagnosed as a case of Gorham's disease following confirmation with histopathology and kept on close follow-up. She was admitted again after 2 years for fever and investigations revealed an absent spleen apart from multicentric osteolytic lesions. This is the first case reported of a child with Gorham's disease who has had an auto-splenectomy on follow-up. Key words: Gorham's disease (disappearing bone disease), osteolytic lesions, spleen. doi: 10.3126/jnps.v29i2.2047 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.94-97